Content Forms and Information Presentation in Virtual Reality - Case: Communicating the Sustainability of Cruise Ships - Seppälä, Kaapo; Könnölä, Kaisa; Krusberg, Markus; Lehtonen, Teijo (United States, 2026)
New technologies open new possibilities to communicate with consumers. Virtual Reality (VR) creates an immersive environment using various content types, from audio to multisensory experiences. In this paper, we wanted to deepen understanding on different ways of sharing information in VR and Metaverse environments; how they are experienced and their effectiveness when different information sharing elements are present. We present the test results of the effect of selected aural and visual content types and their effectiveness in communicating sustainability-related themes to consumers.Combining the logged in-game data with the questionnaire answers, we found out that most players value text as least favourable content form to obtain information in VR environments. However, the learning outcome from text was on a par with the results from other content forms. The youngest age group showed a tendency to advance rapidly in the game, while prematurely quitting the game was observed most often within the eldest user segment. Overall results show a positive attitude towards the idea of presenting sustainability-related content in VR.
Human Factors and Wearable Technologies : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA 26-30 July 2025